Complement activation in wasp venom-induced acute kidney injury - Rui Cheng; Liang Xu; Jianhua Gong; Fanglin Yu; Ying Lv; Hai Yuan; Fengqi Hu (Renal Failure)
Previous studies have highlighted the significant role of complement activation in kidney injuries induced by rhabdomyolysis, intravascular hemolysis, sepsis, and ischemia-reperfusion. Nevertheless, the specific role and mechanism of complement activation in acute kidney injury (AKI) caused by wasp venom remain unclear. The aim of this study was to elucidate the specific complement pathway activated and investigate complement activation in AKI induced by wasp venom. In this study, a complement-depleted mouse model was used to investigate the role of complement in wasp venom-induced AKI. Mice were randomly categorized into control, cobra venom factor (CVF), AKI, and CVF + AKI groups. Compared to the AKI group, the CVF + AKI group showed improved pathological changes in kidneys and reduced blood urea nitrogen (BUN) levels. The expression levels of renal complement 3 (C3), complement 5 (C5), complement 1q (C1q), factor B (FB), mannose-binding lectin (MBL), and C5b-9 in AKI group were upregulated compared with the control group. Conversely, the renal tissue expression levels of C3, C5, C1q, FB, MBL, and C5b-9 were decreased in the CVF + AKI group compared to those in the AKI group. Complement activation occurs through all three pathways in AKI induced by wasp venom. Furthermore, complement depletion by CVF attenuates wasp venom-induced nephrotoxicity, suggesting that complement activation plays a primary role in the pathogenesis of wasp venom-induced AKI.